2017
DOI: 10.1590/1517-869220172305170768
|View full text |Cite
|
Sign up to set email alerts
|

Knee Isokinetic Torque Imbalance in Female Futsal Players

Abstract: Introduction: The specificity of sports training can lead to muscle specialization with a possible change in the natural hamstring/quadriceps torque ratio (HQ ratio), constituting a risk factor for muscle injury at the joint angles in which muscle imbalance may impair dynamic stability. Objective: The aim was to evaluate the torque distribution of the hamstrings and quadriceps and the HQ ratio throughout the range of motion in order to identify possible muscle imbalances at the knee of female futsal athletes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The quadriceps strain had a higher incidence than hamstring strains, as well as other female team sports [25]. In this regard, muscular imbalances have been found in female futsal players in the hamstrings:quadriceps ratio, which was previously identified as a risk factor [26]. The ankle sprain has been reviewed in the literature because of its relevance and recurrence, particularly in women and players of indoor court sport [27], like futsal.…”
Section: Discussionmentioning
confidence: 99%
“…The quadriceps strain had a higher incidence than hamstring strains, as well as other female team sports [25]. In this regard, muscular imbalances have been found in female futsal players in the hamstrings:quadriceps ratio, which was previously identified as a risk factor [26]. The ankle sprain has been reviewed in the literature because of its relevance and recurrence, particularly in women and players of indoor court sport [27], like futsal.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated differences between uninjured and injured participants in FMS total scores and individual FMS test scores such as deep squat (Butler et al, 2013;Chorba et al, 2010;Peate et al, 2007). Prior researcher reported that experienced rugby athletes with FMS composite scores 14 or less were significantly more likely to sustain time-loss injury in a competitive season than those scoring above 14 (Rodrigues et al, 2017). Muscle strength imbalance associated with injury risk (Edouard et al, 2013;Knapik et al, 1991), is likely to negatively affect athletic performance (Maly, Zahalka, & Mala, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…O cálculo da razão flexores/ extensores comumente é realizado por meio do pico de torque desses grupos musculares. Rodrigues (21) e Rodrigues et al (42) propõem calcular a razão levando em consideração os valores de torque extensor e flexor obtidos na mesma amplitude de movimento devido a produção de torque muscular variar de acordo com o ângulo do joelho (54).…”
Section: Análise Estatísticaunclassified
“…No presente estudo os ângulos em que foi encontrado o pico de torque extensor variam de 50° a 80°, que corresponde a faixa que abrange o ângulo ótimo (71,3°), enquanto os ângulos referentes ao pico de torque flexor variam de 33° a 71°, não corresponde à faixa referente ao ângulo ótimo (30,1°) (9,45,(55)(56)(57). As discordâncias dos ângulos flexores podem decorrer da necessidade de maior produção de torque desse grupo muscular em torno dessa amplitude na prática do futsal (42).…”
Section: Análise Estatísticaunclassified
See 1 more Smart Citation